Indian Diabetes Risk Score (IDRS) as a strong predictor of diabetes mellitus: A cross sectional study among urban population of Jhalawar, Rajasthan - Jain, Mayank; Kumar, Vinod; Jain, Manish; Garg, Kapil; Shekhawat, Ravi; Gupta, Pankaj Kumar (Indian Journal of Community Health, 2022)
Introduction: The patients with Type 2 diabetes Mellitus may often remain asymptomatic for a longer period of time. The Indian Diabetes Risk Score (IDRS), a simple screening tool for prediction of undiagnosed diabetes. Objective: Validation of IDRS with standard test for type 2 diabetes among urban population of Jhalawar, Rajasthan. Material and Methods: A Community based Cross-sectional study was carried out in urban field practice area of Department of Community Medicine, Jhalawar Medical College, Jhalawar, Rajasthan. The study was conducted using a two-stage sampling design. A predesigned, pretested proforma and Indian Diabetes Risk Score (IDRS) sheet was used to collect data from the study participants. The IDRS is based on four parameters: age, family history of diabetes, waist circumference and physical inactivity. Data was collected using the World Health Organization stepwise approach to surveillance (STEPS). Results: Among 450 participants, 12.7% participants were in low risk, 59.1% were in moderate risk and 28.2% were in high risk of developing diabetes according to IDRS score. IDRS score of ?60 turned out to be the best cut point for identifying undiagnosed diabetes with sensitivity 92.3% and specificity 82.6%. Positive Predictive value and Negative Predictive value were 47.3% and 98.5% respectively. Conclusion: Association of IDRS was found significant with diabetes. IDRS score of ?60 turned out to be the best cut point for identifying undiagnosed diabetes. IDRS is found valid screening tool for early detection of Diabetes.